eHealth in Care Coordination for Older Adults Living at Home: Scoping Review - Hilde Marie Hunsbedt Fjellså; Anne Marie Lunde Husebø; Marianne Storm (JMIR Publications, 2022)
BackgroundThe population of older adults is projected to increase, potentially resulting in more older adults living with chronic illnesses or multimorbidity. Living with chronic illnesses increases the need for coordinated health care services. Older adults want to manage their illnesses themselves, and many are positive about using eHealth for care coordination (CC). CC can help older adults navigate the health care system and improve information sharing. ObjectiveThis study aimed to map the research literature on eHealth used in CC for older adults living at home. This study assessed CC activities, outcomes, and factors influencing the use of eHealth in CC reported by older adults and health care professionals. MethodsWe used a scoping review methodology. We searched four databases-MEDLINE, CINAHL, Academic Scoping Premier, and Scopus-from 2009 to 2021 for research articles. We screened 630 records using the inclusion criteria (older adults aged >65 years, primary health care setting, description of an eHealth program or intervention or measure or experiences with the use of eHealth, and inclusion of CC or relevant activities as described in the Care Coordination Atlas). The analysis of the included articles consisted of both a descriptive and thematic analysis. ResultsA total of 16 studies were included in this scoping review. Of these 16 studies, 12 (75%) had a quantitative design, and the samples of the included studies varied in size. The categories of eHealth used for CC among older adults living at home were electronic health records and patient portals, telehealth monitoring solutions, and telephone only. The CC activity communication was evident in all studies (16/16, 100%). The results on patient- and system-level outcomes were mixed; however, most studies (7/16, 44%) reported improved mental and physical health and reduced rehospitalization and hospital admission rates. Observing changes in patients' health was a facilitator for health care professionals using eHealth in CC. When using eHealth in CC, available support to the patient, personal continuity, and a sense of security and safety were facilitators for older adults. Individual characteristics and lack of experience, confidence, and knowledge were barriers to older adults' use of eHealth. Health care professionals reported barriers such as increased workload and hampered communication. ConclusionsWe mapped the research literature on eHealth-enabled CC for older adults living at home. We did not map the gray literature as we aimed to map the research literature (peer-reviewed research articles published in academic journals). The study results showed that using eHealth to coordinate care for older adults who live at home is promising. To ensure the successful use of eHealth in CC, we recommend customized eHealth-enabled health care services for older adults, including individualized education and support.